Impact of Climate Resilient Technological Interventions in Jodhpur District of Rajasthan (Indian Journal of Extension Education, 2023)
The agriculture practices in Rajasthan are difficult due to high temperature and low rainfall. The Technology Demonstration Component of National Innovation on Climate resilient Agriculture Project was implemented through KVK, CAZRI, Jodhpur to address climate change issues and improving livelihood of farmers of the region. The study was conducted during 2021-22 and 120 respondents were selected randomly from two villages of Jodhpur district of Rajasthan, to access utility of the services, adoption status and outcome of technological interventions of NICRA. The utility of supply of seeds and critical inputs was perceived as most useful followed by animal health care, availability of farm machinery respectively. The adoption of short duration and drought tolerant varieties of kharif crops lead to 34.20 per cent average yield increase. The adoption of improved breeds and mmineral mixture supplements & multi-nutrient feed block accorded second and third respectively on the basis of extent of adoption. The cropping intensity was increased by 18.52 per cent and employment (man days) increased by 16.80 per cent after NICRA interventions. Per family annual income increased by 65.17 per cent and average savings increased by 80 per cent after the NICRA project.